2004
DOI: 10.1080/09397140.2004.10638064
|View full text |Cite
|
Sign up to set email alerts
|

Variation in the diet of Mehely’s Horseshoe Bat,Rhinolophus mehelyi, in three contrasting environments in western Iran

Abstract: The diet of Rhinolophus mehelyi was investigated through analysis of droppings collected from three maternity roosts in northern Zagros, mid-Zagros and the northern Mesopotamian plain. Moths (Lepidoptera) dominated in all areas (34.9-69.5% volume). The second most important food items in the northern Mesopotamian plain and the mid-Zagros are beetles (Coleoptera, 12.6-28.2% volume), while in northern Zagros Homoptera (16% volume) are the next important food items. The diet of R. mehelyi in northern Zagros is ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…mehelyi and R . eurale , the bulk of the diet of both species in sympatric and allopatric conditions consist of moths [34,39,46,47]. Moreover, in sympatry we found that intra-specific trophic overlap of R .…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…mehelyi and R . eurale , the bulk of the diet of both species in sympatric and allopatric conditions consist of moths [34,39,46,47]. Moreover, in sympatry we found that intra-specific trophic overlap of R .…”
Section: Resultsmentioning
confidence: 88%
“…mehelyi and R . euryale observed elsewhere can also be explained by local variability of available prey [34,37,44-47]. …”
Section: Resultsmentioning
confidence: 99%
“…In several emerge counts performed in this cave it was seen that a population of approximately 700 bat of at least four species including Myotis blythii, Rhinolophus mehelyi, Miniopterus schreibersii, and Myotis cappachinii, roost in this cave. Kermanshah is amongst the medium-size cities in Iran which still support a diverse bat populations and most bats emerging from Mahidasht Cave were observed to heading toward the city (Sharifi and Hemmati 2004).…”
Section: Methodsmentioning
confidence: 99%
“…7 and 8). The bats of the study region are from Rhinolophidae and Rhinolophus Mehely species and their food includes insect and mainly Lepidoptera and herbal material (Sharifi & Hemmati 2004). There is a very strong relationship between the prevailing climate conditions, the growth and the number of bat accumulation regarding the density and frequency of insects as food (Hoying & Kunz 1998;Hood et al 2002).…”
Section: Interpretation Of Palaeoclimate Using Historical and Environmentioning
confidence: 99%